Estimation of Vitamin C Concentration in Commercially Available Fruit Juices from Various Countries Using Iodine Titration - Haniya Muammar Khalifa; Fatma Abdurahman; Bassam Issa Salem Mohamed Aboghalia; Nahid Abdulsalam Alzarouq Amhimmid (African Journal of Advanced Pure and Applied Sciences, 2025)
This study quantified vitamin C (ascorbic acid) concentrations in six commercially available fruit juices from Libya, Saudi Arabia, Lebanon, and Turkey using iodine titration. Samples included single-fruit and mixed juices: Basil, Zain (cocktail), Rauch (Libya), Mizo (Saudi Arabia), Biko (Lebanon), and Daren (Turkey; orange). Results revealed significant variability, with Daren orange juice containing the highest concentration (138.45 mg/200 ml). The findings highlight the influence of juice type, regional fortification practices, and processing on vitamin C content, underscoring the need for standardized labeling to inform consumer choices.